(untitled) (Research, Society and Development, 2022)
This study’s aim was to verify if the site of sexed semen deposition influences the quantity and quality of embryos from superovulated Nelore cows. Twelve females of proved ciclicity were used and went through SOV, FTAI and embryo collection protocols. FTAI was performed at 18 and 30h after the gonadorelin shot, with two straws each one containing 2,1x106 sperm cells, and the embryo collection was done seven days after the gonadorelin shot. Two repetitions were done, in a cross over design, according to semen deposition site, body or uterine horns. At the end of the treatment, 12.00 ± 2.95 and 12.25 ± 4.37 follicles were identified, with mean diameter of 8.64 ± 2.46 and 8.73 ± 2.42mm, for the groups inseminated in the uterine body and horns, respectively. It was noted that 66.7% (8/12) of the animals had CLs at the day of FTAI, presenting four animals in each group. The group inseminated in the uterine body had embryo recovery rate of 41.07% (23/56) and the group inseminated in the uterine horns had 35.71% (15/42). It was seen a decrease in the embryo recovery rate between repetitions, where the first repetition achieved 44.26% (27/61) while the second showed embryo recovery rate of 29.72% (11/37). Yielded 52.17% (12/23) of viable embryos for the group inseminated in the uterine body and 60% (9/15) for the group inseminated in the uterine horns. It was concluded that there weren’t differences at quantity or quality of recovered embryos according to the sexed semen deposition site at the time of FTAI.